2020
DOI: 10.3171/2019.8.jns191219
|View full text |Cite
|
Sign up to set email alerts
|

Gender disparities in academic rank achievement in neurosurgery: a critical assessment

Abstract: OBJECTIVEThe objective of this study was to evaluate whether there are disparities in academic rank and promotion between men and women neurosurgeons.METHODSThe profiles of faculty members from 50 academic neurosurgery programs were reviewed to identify years in practice, number of PubMed-indexed publications, Doctor of Philosophy (PhD) attainment, and academic rank. The number of publications at each acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…Open access have demonstrated that women are less likely than men to be full professors even after adjusting for clinical and academic productivity. [16][17][18] The current literature on gender bias in academic medicine is limited to single studies that assess one institution, 19 20 specialty [21][22][23][24] or country. [25][26][27][28][29] Furthermore, the cross-sectional nature of most analyses precludes an investigation of trends over time.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Open access have demonstrated that women are less likely than men to be full professors even after adjusting for clinical and academic productivity. [16][17][18] The current literature on gender bias in academic medicine is limited to single studies that assess one institution, 19 20 specialty [21][22][23][24] or country. [25][26][27][28][29] Furthermore, the cross-sectional nature of most analyses precludes an investigation of trends over time.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Seven studies adjusted for potential confounders, including years in practice (Dossani et al, 17 Gawad et al, 18 Jena et al, 16 Orhurhu et al, 53 Riaz et al, 54 Smith et al 55 3).…”
Section: Meta-analysis Of Full Professorshipmentioning
confidence: 99%
“…
StrideS have been made in achieving gender parity as the medical literature has addressed the need for more women in the realm of organized neurosurgery. [1][2][3][4][5][6][7][8][9][10][11] Even though more than half of the students in US medical schools are women, smaller percentages of those graduates enter neurosurgical training, remain in academic neurosurgery, and complete fellowship training. 3,12 A white paper regarding neurosurgery residency retention rates by Women in Neurosurgery, called for by the American Association of Neurological Surgeons (AANS), found that medical students have concerns regarding how gender inequities impact acceptance, income, and promotional opportunities within neurosurgery.
…”
mentioning
confidence: 99%
“…She has published numerous papers examining gender differences in neurosurgery, from the medical student to the attending level. [38][39][40][41] She has been instrumental in increasing the percentage of female neurosurgeons so that one day we are no longer "less than a minority," as Robert Spetzler famously stated in his outstanding paper on the history of women in neurosurgery. 42 She is a leader in spine surgery, spinal cord injury, and the socioeconomics of spine surgery.…”
Section: Deborah Benzil MDmentioning
confidence: 99%